URBAN PLANNING ASPECTS OF AIRPORT RECONSTRUCTION: TECHNIQUES OF THE AIRPORT CLUSTER CONCEPTS EFFICIENCY EVALUATION - Tymoshenko, Maria; Marintseva, Kristina (Proceedings of National Aviation University (archive), 2017)
The purpose of this paper is to discuss the techniques of evaluating the efficiency of the airport cluster concepts. Methods: methods of urban, territorial and transport planning and the fuzzy set theory. Results: the fuzzy system of airport selection for implementation of airport cluster concepts was modeled in uncertainty conditions using the Fuzzy Logic Toolbox. Rule Viewer and Surface Viewer graphic tools were used for developing a fuzzy conclusion system in the interactive mode. It was concluded that the combination of a few factors positive for the project with the expectation of change of the land purpose near the airport reduces the efficiency of decisions to create the airport-cluster with a conditional maximum score of "1" to "0.4". Discussion: airport-centered concepts are still insufficiently investigated in terms of the implementation effectiveness. The use of fuzzy set theory techniques requires a preliminary decomposition of the task within the framework of the airport-centered concept subject to involvement of experts from various fields knowledge. The basis for substantiated expert assessments to construct the membership functions should be a preliminary implementation of a few feasibility tasks.